The effect of seed inoculation with mycorrhizal fungi on germination and growth indicators of two papaya varieties in different culture substrates - Ali najm; Mehdi Aran; Abdolrahman Rahimian Boogar Rahimian Boogar (علوم و فناوری بذر ایران, 2023)
This experiment was conducted to investigate the germination and seedling growth of two papaya (Carica papaya L.) varieties in response to the inoculation of mycorrhizal fungi and culture substrates in a factorial in the form of a completely randomized design. The experiment factors include varieties at 2 levels (Red Lady (V1) and Bangladeshi (V2)), culture substrate at 5 levels (compost + perlite + vermicompost (1:1:1) (S1), compost + perlite + cocopeat (1:1:1) (S2), compost + vermicompost + cocopeat (1:1:1) (S3), perlite + vermicompost + cocopeat (1:1:1) (S4) and compost + perlite + vermicompost + cocopeat (1:1:1:1) (S5)), and mycorrhizal at 2 levels (no inoculation as control (M0) and inoculation (M1)). The results indicated a significant effect of culture substrate and mycorrhizal on germination and growth characteristics of papaya varieties. In the mycorrhizal inoculation treatment, the highest germination percentage (77.33%) and germination speed index (0.63) were observed in the Bangladeshi variety and the lowest average germination time for both varieties . The highest seedling height and root length were recorded for V1S4M1 and V2S5M1 treatments, and the highest shoot dry weight (0.276 g) was recorded for V2S5M1 treatment. According to the obtained results, inoculation of seeds in both Red Lady and Bangladeshi papaya varieties with mycorrhizal fungi and substrates containing organic matter, especially vermicompost, improved the germination and growth characteristics of the seedlings. Therefore, according to the advantages and compatibility of mycorrhizal fungi, it can be used as a suitable treatment to improve the germination and growth of papaya seedlings.